Histologis Testis pada Keturunan F1 dari Induk Puyuh (Coturnix coturnix japonica L.) yang diberi Suplemen Serbuk Kunyit (Curcuma longa L.) dalam Pakan - Waty, Mitra; Tana, Silvana; Saraswati, Tyas Rini (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Quail child has a tremendous potential to continue further descent because quails have almost all the potential that can be exploited by humans, either for consumption or economic. Children quail superior quality can be produced from superior quality parent, so the parent quail quality must be considered. Additional food in the form of powder turmeric supplements can increase the phytoestrogen which stimulates the liver to produce vitellogenin as the material forming the yolk. Egg yolk is a source of nutrients for the development of quail embryos. This study aimed to analyze the differences in the quality of the parent male quail chicks were given supplements of turmeric powder to the testis weight, testis size, number of spermatogonia and spermatids amount contained in the seminiferous tubules. The study design used was completely randomized design (CRD) that is 3 treatments and 5 replications. By using quail male child as much as 15 tails as test animals, divided into three groups, namely K0: F1 generation of the female quail are not given turmeric powder supplement, K1: F1 generation of the female quail turmeric powder supplemented with a dose of 54 mg/tail/day and K2: kuturunan F1 of the parent quail turmeric powder supplemented with a dose of 108 mg/tail/day. The variables measured were testis weight, testis size, number of spermatogonia and spermatids number. Data were analyzed using Analysis of Variance (ANOVA) followed by a further test Duncan Multiple Range Test (DMRT) at the 95% significance level. The results showed that the quality of parent child quail turmeric powder supplemented with a dose of 108 mg/tail/day for better views of the process of spermatogenesis. Keywords: Child quail (Coturnix coturnix japonica. L), Turmeric, Testis, spermatogonia, spermatids.